In vitro methane production and fermentative characteristics from temperate and tropical grasses - Rivas-Martínez, Mayra Iliana; Cobos- Peralta, Mario Antonio; Ley-de Coss, Alejandro; Bárcena- Gama, José Ricardo; González- Muñoz, Sergio Segundo (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of this research was to evaluate in vitro methane (CH4) production, carbon dioxide (CO2), and fermentative variables from template and tropical grasses: The experiment was designed as a randomized complete design, CH4 and CO2 were higher in tropical grasses (199.20, 55.78, and 121.58 mL g Dry matter, DM) compared template grasses (61.87, 26.6 and 52.9 mL g DM−1 respectively). Volatile fatty acid production was highest (P < 0,05) from template grasses. However, acetic acid production considered a precursor to CH4 was mayor from tropical grass. pH and total bacteria population were similar by grasses. The conclusions were: evaluated tropical grasses increased the biogas production per gram of dry matter fermented and acetic acid amount and consequently the methane production was incremented.
Keywords: Keywords: enteric fermentation: climate-smart livestock; greenhouse gases; ruminants.